2014
DOI: 10.3389/fpubh.2014.00016
|View full text |Cite
|
Sign up to set email alerts
|

From Public Mental Health to Community Oral Health: The Impact of Dental Anxiety and Fear on Dental Status

Abstract: Dental fear is a widely experienced problem. Through a “vicious cycle dynamic,” fear of dental treatment, lower use of dental services, and oral health diseases reinforce each other. Research on the antecedents of dental anxiety could help to break this cycle, providing useful knowledge to design effective community programs aimed at preventing dental fear and its oral health-related consequences. In this regard, frameworks that analyze the interplay between cognitive and psychosocial determinants of fear, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
0
54
0
1
Order By: Relevance
“…Previous research has shown that dental anxiety is not only a mental health issue but a public health concern . Fear of dental treatment leads to irregular or delayed dental visits, increasing the risk of caries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that dental anxiety is not only a mental health issue but a public health concern . Fear of dental treatment leads to irregular or delayed dental visits, increasing the risk of caries .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that dental anxiety is not only a mental health issue but a public health concern . Fear of dental treatment leads to irregular or delayed dental visits, increasing the risk of caries . Although several investigations have evaluated oral health causal factors, the majority have focused on diet, the oral microflora and preventive dental measures …”
Section: Introductionmentioning
confidence: 99%
“…Childhood dental anxiety occurs in different countries and among different ethnicities, with a 6%–20% incidence (Klingberg & Broberg, ). This issue results in significant deterioration of oral health and leads to a vicious cycle (Crego, Carrillo‐Díaz, Armfield, & Romero, ) of cumulative anxiety and increased avoidance (Lin, ). The parents of children with the most severe dental anxiety may defer, cancel, or miss their child’s dental appointments (Mark, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, fear of blood and needles represents an important individual and public health concern as it is a documented deterrent to procedures such as routine blood work [22,38], insulin injections and finger sticks for diabetes management [13,39], dental care [7,25], vaccinations [21,32,38], and blood donation [38]. A severe form of this fear -termed blood-injection-injury phobia -is characterized by an intense fear of blood, injections, medical care, and injury; such fear is recognized as excessive and unreasonable by the individual [1].…”
Section: Introductionmentioning
confidence: 99%